Changes in Modern Family Life and Determinants Transformation of Family - Milivojević, Snežana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2014)
The theoretical framework of this topic can be built on an analysis of the following issues: developmental changes in the family, the transformation function of a modern family, such changes in the structure of families and relationships among its members, the transition model of marriage and parenting, the impact of social, economic and demographic factors on the transformation of the family Review and prospects for the future development of the family, to be able to point out the changes in marriage and parenthood, which, under the influence of these factors influence the changing functions of the family, its structure and sl.U postmodern society there has been a convergence of roles between men and women in terms of education , employment, economic independence, career and family, bringing about a different perspective on marriage, or different idea about marriage and acceptance of different values from those who have had previous generations, changing people's attitudes about marriage, sexual behavior, and the like. For young people, especially women, a desire for independence and self-fulfillment, both on the job and through various arrangements of family and marriage forms, and greater willingness to experiment with different life practices related to communal life than previous generations.
Keywords: changes; transitional societies; modern family; independence; family life